Chapters from the History of the Hungarian Ministry of Justice in World War II - Antal, Tamás (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2020)
The author deals with four special issues from the history of the Ministry of Justice during the period mentioned in the title: the jurisdictional challenges in connection with the re-occupation of the so-called Southern Territories which were lost by the Treaty of Trianon; the scope of authority and the duties of the Service for National Policy organized in 1940; the new task of the Supervising Authority of Public Interests coming from the implementation of the Jewish laws; finally the mission of Minister Gábor Vladár at the end of the Horthy era.